Long-range electrostatic screening in ionic liquids - Gebbie, Matthew A. (Proc Natl Acad Sci U S A, 2015)
Electrolyte solutions with high concentrations of ions are prevalent in biological systems and energy storage technologies. Nevertheless, the high interaction free energy and long-range nature of electrostatic interactions makes the development of a general conceptual picture of concentrated electrolytes a significant challenge. In this work, we study ionic liquids, single-component liquids composed solely of ions, in an attempt to provide a novel perspective on electrostatic screening in very high concentration (nonideal) electrolytes. We use temperature-dependent surface force measurements to demonstrate that the long-range, exponentially decaying diffuse double-layer forces observed across ionic liquids exhibit a pronounced temperature dependence: Increasing the temperature decreases the measured exponential (Debye) decay length, implying an increase in the thermally driven effective free-ion concentration in the bulk ionic liquids. We use our quantitative results to propose a general model of long-range electrostatic screening in ionic liquids, where thermally activated charge fluctuations, either free ions or correlated domains (quasiparticles), take on the role of ions in traditional dilute electrolyte solutions. This picture represents a crucial step toward resolving several inconsistencies surrounding electrostatic screening and charge transport in ionic liquids that have impeded progress within the interdisciplinary ionic liquids community. More broadly, our work provides a previously unidentified way of envisioning highly concentrated electrolytes, with implications for diverse areas of inquiry, ranging from designing electrochemical devices to rationalizing electrostatic interactions in biological systems.